New visions for metropolitan America - Downs, Anthony 1930-2021 (Brookings Inst. u.a., 1994)
In this book, Anthony Downs identifies growth-related problems and examines current efforts to control growth. He explains that individual suburban governments have reacted with policies intended to manage local growth; but those policies taken together have actually aggravated problems at the regional level. The most dangerous result of growth management policies is that they help perpetuate the concentration of very poor households in depressed neighborhoods in big cities and older suburbs. These neighborhoods are riddled with exploding rates of crime and violence, increased numbers of children growing up in poverty, poor-quality public education, and many workers excluded from the mainstream work force